Metal packaged micro-mesoporous hierarchical pore molecular sieve catalyst, preparation method and application thereof, and method for synthesizing 1, 3-propylene glycol

By designing a metal-encapsulated micro-intermediate multi-stage porous molecular sieve structure in the catalyst, the interlayer of W oxide and Pt nanoparticles is supported and fixed with a shell of zeolite molecular sieve, the problem of easy deactivation of the active components of the catalyst in hydrothermal reaction is solved, and the high stability and industrial application of the catalyst are achieved.

CN119909734APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311436534.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The active components of existing catalysts are prone to agglomeration and loss in hydrothermal reactions, resulting in catalyst deactivation and difficult to meet industrial needs.

Method used

The metal-encapsulated micro-intermediate multi-stage porous molecular sieve catalyst is used to load the sandwich structure of W oxides and Pt nanoparticles, and the active components are fixed with the shell of the zeolite molecular sieve to avoid their aggregation and loss.

Benefits of technology

It achieves high stability of the catalyst under hydrothermal conditions and long-term operation activity maintenance, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909734A_ABST
    Figure CN119909734A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalyst material synthesis, and discloses a metal packaged micro-mesoporous hierarchical pore molecular sieve catalyst, a preparation method and application thereof, and a method for synthesizing 1, 3-propylene glycol, the catalyst comprises a molecular sieve seed crystal inner core, an interlayer containing active components, and a molecular sieve shell; wherein the interlayer containing the active component comprises W oxide and Pt nano particles. The catalyst has a stable metal encapsulated micro-mesoporous hierarchical pore structure, has relatively high hydrothermal stability, can maintain the catalytic activity of active components under long-period operation, and is suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst material synthesis, and in particular to a metal-encapsulated micro-meso-multilevel pore molecular sieve catalyst, a preparation method and application thereof, and a method for synthesizing 1,3-propylene glycol. Background Art

[0002] At present, with the development of the polyester industry, the homogenization problem of low-end polyester has intensified, and it is necessary to develop new polyester monomers to promote the upgrading of the industry. Biodiesel is obtained by the exchange reaction of glycerol fatty acids and methanol esters. During the reaction process, 1.2 kg of by-product glycerol will be generated for every 10 kg of biodiesel produced. The effective use of glycerol, for example, using it to produce some high-value-added high-end chemicals, will be a good choice in terms of economy, environmental protection and resource recycling. Among them, the selective synthesis of high-value-added 1,3-propylene glycol from glycerol is one of the most economically promising and socially valuable paths. 1,3-propylene glycol is an important monomer for the production of poly(1,3-propylene terephthalate) (PTT). PTT has the advantages of easy processing of polyethylene terephthalate (PET) and high performance of poly(butylene terephthalate) (PBT). It is a high-end polymer product that can produce high-end plastic medical products and fabrics. Therefore, the use of by-product glycerol obtained in the production process of biodiesel to synthesize high-value-added 1,3-propylene glycol has the advantages of green, environmental protection and sustainable development.

[0003] 1,3-propylene glycol was initially industrialized through chemical synthesis, including Shell's ethylene oxide carbonylation hydrogenation method and Degussa and Dupont's acrolein hydration hydrogenation method. However, due to the complex process, environmental pollution, and difficulty in catalyst synthesis, the above methods have been discontinued in the context of global carbon reduction. DuPont (CN200380104657.2) discloses a production pathway for converting sugar sources into 1,3-propylene glycol through a biological fermentation method, but this method requires the addition of expensive vitamin B12, which is costly; Tsinghua University (CN200510011867.8) discloses a method for biologically converting glycerol into 1,3-propylene glycol using Clostridiurn strains. However, the biological synthesis of 1,3-propylene glycol faces common and difficult-to-solve problems, namely, the method is affected by the metabolic activity of the organism, the production efficiency is low, and the product is complex, containing vitamins, salts, strains and other impurities, and the separation process requires multiple steps, and the separation cost is high. It is difficult to reduce the price of 1,3-propylene glycol, which makes the price of 1,3-propylene glycol high, hindering its large-scale application. On the contrary, the production of high-value-added 1,3-propylene glycol using bio-based glycerol has the advantages of high-concentration glycerol feed, simple process, and easy method. It can overcome the shortcomings of biological methods, break through the technical bottleneck of this path, and achieve industrialization, which has huge economic benefits and scientific research value.

[0004] The technical pain point that hinders the industrialization of this technology is the lack of efficient and stable catalysts. The current catalysts have the following main problems: the catalysts with better activity all use W and Pt as the main active components. However, because water is used as the solvent in the reaction system, the W and Pt components are easy to agglomerate and lose under the hydrothermal reaction conditions, causing the catalyst to deactivate quickly, making it difficult to meet the needs of industrialization, so that the research on this topic has been in the laboratory research stage.

[0005] Therefore, it is necessary to solve the common problem of stability of active components of supported catalysts in aqueous reaction environments. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem that the active components of the catalyst for synthesizing 1,3-propylene glycol in the hydrothermal reaction of the prior art are easily agglomerated and lost, and the catalyst will be deactivated during long-term operation. A metal-encapsulated micro-meso-multilevel pore molecular sieve catalyst and its preparation method and application, and a method for synthesizing 1,3-propylene glycol are provided. The catalyst has a stable metal-encapsulated micro-meso-multilevel pore structure, has high hydrothermal stability, can maintain the catalytic activity of the active components during long-term operation, and is suitable for industrial application.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst, wherein the catalyst comprises a molecular sieve seed core, an interlayer containing active components and a zeolite molecular sieve shell;

[0008] Wherein, the interlayer containing active components includes W oxide and Pt nanoparticles.

[0009] A second aspect of the present invention provides a method for preparing a metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst, wherein the method comprises:

[0010] (1) loading W oxide and Pt nanoparticles on the molecular sieve seed core to obtain a first pre-product;

[0011] (2) subjecting a mixed solution containing the first pre-product, the first alkali source, the structure directing agent, the silicon source, the aluminum source and water to a crystallization reaction to obtain a second pre-product;

[0012] (3) heat-treating the second pre-product to obtain a molecular sieve catalyst.

[0013] The third aspect of the present invention provides a metal-encapsulated micro-mesoporous molecular sieve catalyst prepared by the preparation method described in the second aspect.

[0014] The fourth aspect of the present invention provides an application of the metal-encapsulated micro-mesoporous molecular sieve catalyst described in the first aspect or the third aspect in the reaction of synthesizing 1,3-propylene glycol.

[0015] A fifth aspect of the present invention provides a method for synthesizing 1,3-propylene glycol, wherein the method comprises: contacting a glycerol aqueous solution with the metal-encapsulated micro-mesoporous hierarchical pore molecular sieve catalyst described in the first aspect or the third aspect to react.

[0016] Through the above technical solution, the beneficial effects obtained are as follows:

[0017] (1) The metal-encapsulated micro-mesoporous catalyst provided by the present invention has a sandwich structure with W oxide and Pt nanoparticles as active components. The outer shell uses an in-situ grown zeolite molecular sieve to anchor the active components, thereby avoiding the aggregation and loss of Pt and W active components. The catalyst has excellent hydrothermal stability;

[0018] (2) In the present invention, the method for preparing the catalyst is simple, and W oxide and Pt nanoparticles are loaded onto the molecular sieve seed core of the catalyst by a specific loading method, and the loading amount of W oxide and Pt nanoparticles can be flexibly adjusted. The zeolite molecular sieve of the outer shell is synthesized by crystallization reaction, which plays a better role in fixing the W oxide and Pt nanoparticles in the interlayer;

[0019] (3) In the present invention, preferably, when the metal-encapsulated micro-mesoporous molecular sieve catalyst is used in the reaction of synthesizing 1,3-propylene glycol from glycerol, the activity of the catalyst and the stability of long-term operation are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a TEM image of the metal-encapsulated micro-mesoporous multi-level molecular sieve catalyst of Example 1;

[0021] Figure 2 This is the pore distribution diagram of the metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst of Example 1. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] The first aspect of the present invention provides a metal-encapsulated micro-mesoporous molecular sieve catalyst, wherein the catalyst comprises a molecular sieve seed core, an interlayer containing active components and a molecular sieve shell;

[0024] Wherein, the interlayer containing active components includes W oxide and Pt nanoparticles.

[0025] In the present invention, the innermost layer of the metal package micro-meso-multi-level pores is a molecular sieve seed kernel, the middle interlayer is coated outside the kernel, and the outermost layer of the interlayer is an in-situ grown molecular sieve shell. The above-mentioned structural catalyst has a more stable structure and has high hydrothermal stability. The interlayer uses W oxide and Pt nanoparticles as active components, and the molecular sieve shell of the shell anchors the active components of the interlayer to avoid the aggregation and loss of active components. During the crystallization process, micro-meso-multi-level pores are formed, which is conducive to mass transfer and can improve catalytic activity.

[0026] According to the present invention, the type of the molecular sieve seed kernel is not particularly limited, and is a conventional zeolite molecular sieve in the art. Preferably, the molecular sieve seed kernel is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, preferably Beta molecular sieve and / or HY molecular sieve. The above-mentioned zeolite molecular sieve is used as the molecular sieve seed kernel, which has good hydrothermal stability, and after loading the active metal, the active component is relatively stable.

[0027] In the present invention, the molecular sieve silicon-aluminum molar ratio SiO2 / Al2O3 of the molecular sieve seed crystal core is not particularly limited, and is preferably 5-200, and more preferably 10-100.

[0028] In the present invention, the source of the molecular sieve seed core is not particularly limited and can be purchased commercially or prepared by existing methods.

[0029] According to the present invention, preferably, the average particle size of the molecular sieve seed kernel is 0.1-10 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 7 μm, 10 μm, or any range between the two, preferably 0.2-2 μm. The active components of the interlayer are loaded on the above-mentioned kernel, and the active components are evenly dispersed on the surface of the kernel, which can effectively improve the catalytic activity of the catalyst. The average particle size of the molecular sieve seed kernel refers to the average particle size of the kernel particles, and the particles can be single particles or particles formed by agglomeration of several small particles.

[0030] In the present invention, the average particle size of the molecular sieve seed core is measured by SEM method, and the average value is obtained by randomly measuring the size of 100 core particles by NanoMeasurer software. In the measurement process, the average particle size has the conventional interpretation in the art, which refers to the particle size. If it is a spherical particle, it refers to the diameter of the sphere. If it is an irregular particle, it refers to the largest straight-line distance in the particle.

[0031] According to the present invention, preferably, the average particle size of the Pt nanoparticles is 0.5-8nm, such as 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 6nm, 7nm, 8nm, or any range therebetween, preferably 2-4nm. In the present invention, limiting the average particle size of the Pt nanoparticles can make the distribution of the Pt nanoparticles in the interlayer more uniform and the stability of the active component loading better.

[0032] In the present invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the particle sizes of 100 Pt nanoparticles in the transmission electron microscopy image are randomly measured and the average value is obtained.

[0033] In the present invention, the mass percentage of the Pt nanoparticles and the mass percentage of the W oxide in the interlayer of the catalyst are obtained by ICP method testing.

[0034] According to the present invention, preferably, based on the total weight of the catalyst, the mass percentage of the Pt nanoparticles is 0.2-5wt%, for example, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 4wt%, 5wt%, or any range therebetween, preferably 1-2wt%.

[0035] According to the present invention, preferably, based on the total weight of the catalyst, the mass percentage of the W oxide is 0.2-5wt%, for example, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 4wt%, 5wt%, or any range therebetween, preferably 0.5-2wt%.

[0036] In the present invention, an interlayer containing Pt nanoparticles and W oxide is loaded on the molecular sieve seed core, the W oxide provides highly dispersed W adsorption sites, and the Pt nanoparticles provide efficient hydrogen active sites, and the two work together to provide efficient catalytic activity. The W oxide is dispersed on the inner surface and outer surface of the molecular sieve seed core, and the Pt nanoparticles are dispersed on the outer surface of the molecular sieve seed core.

[0037] In the present invention, the thickness of the shell refers to the thickness of the zeolite molecular sieve supported outside the interlayer by in-situ growth.

[0038] According to the present invention, preferably, the thickness of the molecular sieve shell is 5-80nm, preferably 10-30nm. In the present invention, the thickness of the catalyst shell is measured by transmission electron microscopy. Figure 1 As shown, a curve can be drawn with the outer edge position of the Pt nanoparticles, and the distance between the curve and the outer edge of the entire catalyst is the thickness of the catalyst shell. The average value of ten random positions is recorded as the thickness of the shell. The catalyst shell that meets the above definition is more conducive to promoting the crystallization of the outer molecular sieve, fixing the active components of the interlayer, and improving the hydrothermal stability of the catalyst.

[0039] According to the present invention, preferably, the mesopore volume of the metal-encapsulated multi-level pore zeolite molecular sieve is 0.01-0.1m 3 / g, preferably 0.03-0.08m 3 / g; micropore volume is 0.03-0.3m 3 / g, preferably 0.05-0.1m 3 / g. The micropore volume and mesopore volume of the zeolite molecular sieve are measured by low-temperature nitrogen adsorption capacity method, and the test instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics. Test conditions: the sample is vacuum degassed at 1.33Pa and 300℃ for 4h, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, adsorption and desorption isotherms are measured, and the micropore volume and mesopore volume are calculated using the BET formula.

[0040] According to the present invention, the type of the shell molecular sieve is not particularly limited, as long as it can be coated outside the interlayer to form a shell, and is preferably the same type as the molecular sieve seed core. Those skilled in the art can adjust the shell molecular sieve type according to the core and interlayer structure of the catalyst.

[0041] According to the present invention, preferably, the shell molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve. The shell molecular sieve can anchor the active components of the interlayer in the shell and improve the stability of the catalyst under hydrothermal conditions.

[0042] In the present invention, the type of the inner core of the molecular sieve seed crystal is the same as the type of the outer shell molecular sieve.

[0043] A second aspect of the present invention provides a method for preparing a metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst, wherein the method comprises:

[0044] (1) loading W oxide and Pt nanoparticles on the molecular sieve seed core to obtain a first pre-product;

[0045] (2) subjecting a mixed solution containing the first pre-product, the first alkali source, the structure directing agent, the silicon source, the aluminum source and water to a crystallization reaction to obtain a second pre-product;

[0046] (3) heat-treating the second pre-product to obtain a molecular sieve catalyst.

[0047] In the present invention, the interlayer is loaded on the inner core of the molecular sieve seed crystal, and the zeolite molecular sieve shell is obtained by in-situ growth on the outermost layer to form a molecular sieve catalyst with stable metal encapsulation micro-meso-multilevel pores. The preparation method is simple and can flexibly adjust the loading amount of W oxide and Pt nanoparticles in the interlayer. During the crystallization process, micro-meso-multilevel pores are formed, which is more conducive to mass transfer and improves the catalyst activity while improving the stability of the active components.

[0048] According to the present invention, preferably, the loading process in step (1) comprises:

[0049] (1-1) mixing a W precursor solution with a molecular sieve seed core, drying and calcining to obtain a core loaded with W oxide;

[0050] (1-2) The W oxide-loaded core and the Pt nanoparticle solution are mixed and ultrasonically treated, and then dried to obtain a first pre-product.

[0051] In the present invention, step (1) adopts a special loading method to load W oxide and Pt nanoparticles on the molecular sieve seed core, and the Pt nanoparticles are loaded after being synthesized. Compared with the impregnation method, the size of the Pt nanoparticles in the catalyst is controllable, the distribution is uniform, and the catalytic activity and selectivity are high.

[0052] According to the present invention, preferably, the molecular sieve seed crystals are selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, preferably Beta molecular sieve and / or HY molecular sieve.

[0053] According to the present invention, the type of the W precursor is not particularly limited, and any compound that can provide a tungsten source is sufficient. Preferably, the W precursor is selected from at least one of ammonium metatungstate, ammonium paratungstate and sodium tungstate.

[0054] According to the present invention, preferably, the amount of the W precursor added is calculated as oxide, and the mass ratio of the W precursor to the molecular sieve seed core is 1:20-500, for example, 1:20, 1:30, 1:40, 1:50, 1:80, 1:100, 1:150, 1:200, 1:300, 1:400, 1:500, or any range therebetween, preferably 1:50-200.

[0055] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 400-700° C., preferably 500-600° C., and a calcination time of 1-10 h, preferably 2-6 h. Calcination under the above conditions can uniformly load W oxide on the surface of the core to form highly dispersed W active sites.

[0056] According to the present invention, preferably, the mass ratio of the W oxide-loaded core to the Pt nanoparticles is 1:0.002-0.04, for example, 1:0.002, 1:0.005, 1:0.01, 1:0.012, 1:0.015, 1:0.018, 1:0.02, 1:0.03, 1:0.04, or any range therebetween, preferably 1:0.01-0.02.

[0057] The present invention has no specific restrictions on the mixing of step (1-1) and the mixing and ultrasonic conditions of step (1-2), which can be appropriately selected according to the specific situation. Preferably, the mixing is carried out by stirring, and the stirring rate is not particularly limited, as long as the purpose of uniform mixing can be achieved. In the present invention, the method of adding each substance in step (1-2) is not particularly limited, and it can be added separately or together.

[0058] In the present invention, preferably, the process of drying the ultrasonic product after separation is also included. The separation method is not particularly limited. According to a specific embodiment of the present invention, centrifugal separation can be used. The conditions of centrifugal separation are not particularly limited, and those skilled in the art can adjust the conditions according to the separation conditions.

[0059] According to the present invention, preferably, in step (1-2), the drying conditions include: heating temperature of 40-120°C, preferably 60-100°C; heating time of 1-15h, preferably 3-10h. In the present invention, drying under the above conditions will not destroy the activity of the Pt nanoparticles, and at the same time make the Pt nanoparticles uniformly distributed in the interlayer.

[0060] According to the present invention, preferably, the method for preparing the Pt nanoparticle solution comprises: mixing a Pt source, a template and a solvent, and refluxing to obtain a Pt nanoparticle solution.

[0061] According to the present invention, preferably, the amount of the Pt source added is based on the Pt single substance, and the mass ratio of the Pt source: template: solvent is 1: (1-50): (500-10000), preferably 1: (5-30): (1000-5000). By adding the above substances in the above addition amounts, a Pt nanoparticle solution with a more uniform average particle size distribution of Pt nanoparticles can be prepared. Using the above Pt nanoparticle solution, the size of the Pt nanoparticles in the synthesized catalyst is controllable, the distribution is uniform, and the catalytic activity and selectivity are high.

[0062] According to the present invention, preferably, the reflux conditions include: under a protective atmosphere, a reflux temperature of 60-200° C., preferably 80-180° C.; a reflux time of 0.5-6 h, preferably 2-4 h. Reflux under the above conditions can obtain Pt nanoparticles with a more uniform average particle size distribution and a stable Pt nanoparticle solution.

[0063] In the present invention, the type of the protective atmosphere is not particularly limited, and is preferably at least one selected from argon, nitrogen and helium.

[0064] According to the present invention, the type of the Pt source is not particularly limited, and is a conventional Pt-containing compound in the art. Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate, and potassium chloroplatinate.

[0065] According to the present invention, the type of the template is not particularly limited. Preferably, the template is selected from at least one of polyvinyl pyrrolidone, polyethylene imine and oleylamine.

[0066] According to the present invention, the solvent is selected from at least one of a saturated monohydric alcohol having 1 to 3 carbon atoms and a saturated dihydric alcohol having 1 to 3 carbon atoms, preferably selected from at least one of a methanol aqueous solution, an ethanol aqueous solution and a propanol aqueous solution. The volume ratio of alcohol to water in the alcohol aqueous solution is 1:0.05-2, preferably 1:0.1-1.

[0067] According to the present invention, preferably, in step (2), in the mixed solution, the amount of the silicon source added is calculated as SiO2, the amount of the aluminum source added is calculated as Al2O3, and the mass ratio of the first pre-product: the first alkali source: the structure directing agent: the silicon source: the aluminum source: the water is 1: (0.1-10): (0.1-10): (0.05-1): (0.005-0.1): (1-10), preferably 1: (0.2-5): (0.2-5): (0.1-0.5): (0.01-0.05): (2-5).

[0068] According to the present invention, the type of the first alkali source is not particularly limited, and it is sufficient that the silicon source can be hydrolyzed and the synthesis of the molecular sieve shell can be promoted. The skilled person in the art can make an adaptive selection. Preferably, the first alkali source is selected from at least one of ammonia water, sodium hydroxide and potassium hydroxide. The skilled person in the art can adjust the amount of the first alkali source added according to the synthesis of the molecular sieve shell. The addition of sodium hydroxide and / or potassium hydroxide can be a compound or an aqueous solution. When the alkali source is added in the form of an aqueous solution, the amount of the alkali source added is based on the mass of the solute.

[0069] According to the present invention, the type of the structure directing agent is not particularly limited, and is a conventional structure directing agent for synthetic zeolite molecular sieves in the art, and those skilled in the art can adaptably select it according to the type of synthetic molecular sieve shell. Preferably, the structure directing agent is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium bromide and tetrapropylammonium bromide.

[0070] According to the present invention, the type of the silicon source is not particularly limited, and is a conventional silicon source in the art capable of synthesizing zeolite molecular sieves. Preferably, the silicon source is ethyl orthosilicate and / or methyl orthosilicate.

[0071] According to the present invention, the type of the aluminum source is not particularly limited, and is a conventional aluminum source in the art capable of synthesizing zeolite molecular sieves. Preferably, the aluminum source is sodium metaaluminate and / or pseudo-boehmite.

[0072] In the present invention, preferably, the mixing method of the substances in step (2) is not particularly limited, and a mixed solution can be obtained. According to a specific embodiment of the present invention, the mixed solution is obtained by stirring at room temperature. The stirring rate and stirring time are not particularly limited, and those skilled in the art can make adaptive adjustments.

[0073] In the present invention, step (2) further includes an aging process before the crystallization reaction, wherein the aging conditions include: an aging time of 1-16 hours, preferably 5-12 hours. Aging under the above conditions can allow amorphous silicon aluminum to be more evenly coated on the outer layer of the molecular sieve.

[0074] According to the present invention, preferably, the conditions of the crystallization reaction in step (2) include: reaction temperature of 80-240° C., preferably 120-180° C.; reaction time of 2-120 h, preferably 12-36 h.

[0075] In the present invention, there is no particular limitation on the equipment for the crystallization reaction, as long as it can be used under the crystallization reaction conditions, and those skilled in the art can select it as needed. According to a preferred embodiment of the present invention, the crystallization reaction is carried out in a reactor, preferably a hydrothermal reactor.

[0076] In the present invention, preferably, after the crystallization reaction is completed, the reactor is cooled down (preferably to room temperature) and then opened. This preferred embodiment avoids the safety hazard of opening the reactor at high temperature due to the self-generated pressure in the reactor caused by the crystallization reaction under elevated temperature.

[0077] In the present invention, preferably, the second pre-product is separated, dried, and then heat treated. The conditions of separation and drying are not particularly limited and can be adaptively adjusted by those skilled in the art. The heat treatment is performed by calcination.

[0078] According to the present invention, preferably, in step (3), the heat treatment conditions include: a heating temperature of 200-600°C, preferably 300-500°C; and a heating time of 1-10h, preferably 3-6h.

[0079] The third aspect of the present invention provides a metal-encapsulated micro-mesoporous molecular sieve catalyst prepared by the preparation method described in the second aspect.

[0080] The fourth aspect of the present invention provides an application of the metal-encapsulated micro-mesoporous molecular sieve catalyst described in the first aspect or the third aspect in the reaction of synthesizing 1,3-propylene glycol.

[0081] A fifth aspect of the present invention provides a method for synthesizing 1,3-propylene glycol, wherein the method comprises: contacting a glycerol aqueous solution with the metal-encapsulated micro-mesoporous hierarchical pore molecular sieve catalyst described in the first aspect or the third aspect to react.

[0082] In the present invention, preferably, when the catalyst is applied to the reaction of hydrogenolysis of glycerol to produce 1,3-propylene glycol, the activity and cycle stability of the catalyst are significantly improved, the glycerol conversion rate is high, and the selectivity of the synthetic product 1,3-propylene glycol is high.

[0083] In the present invention, there is no particular limitation on the reaction conditions and reaction equipment, and those skilled in the art can select them according to the actual situation of the reaction of synthesizing 1,3-propylene glycol from glycerol. Preferably, the reaction can be carried out in a fixed bed reactor.

[0084] According to the present invention, preferably, the reaction conditions include: reaction temperature of 120-200°C, preferably 150-170°C; hydrogen pressure of 1-6MPa, preferably 3-5MPa; mass concentration of glycerol in the glycerol aqueous solution of 10-95wt%, preferably 40-90wt%; liquid phase mass space velocity of 0.05-5h -1 , preferably 0.1-2h -1 .

[0085] In the present invention, the liquid phase refers to a glycerol aqueous solution.

[0086] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, the reagents and materials used can be obtained commercially, and the room temperature is 25°C;

[0087] Polyvinyl pyrrolidone is Aladdin brand, with a molecular weight of 58,000.

[0088] Example 1

[0089] (1-1) 0.1 g of ammonium metatungstate solution in terms of WO3 was mixed with 10 g of Beta zeolite molecular sieve and stirred for 4 h, wherein the Beta zeolite molecular sieve had an average particle size of 0.2 μm and a silicon-aluminum molar ratio of SiO2 / Al2O3 of 25, and after rotary evaporation drying, the mixture was calcined in air at 550°C for 5 h to obtain a core loaded with W oxide;

[0090] (1-2) 20 mL of water and 180 mL of methanol were placed in a 500 mL round-bottom flask, 0.1 g of Pt was added through an 8 wt % chloroplatinic acid solution, 0.6 g of polyvinyl pyrrolidone (PVP) was added, and the mixture was stirred for 5 min, then heated to 100 °C and refluxed for 3 h under an argon atmosphere to obtain a Pt nanoparticle solution;

[0091] 1 g of the W oxide-loaded core was added to a solution containing 0.02 g of Pt nanoparticles, stirred for 3 h under ultrasonic conditions, centrifuged, and dried at 80 °C for 6 h to obtain the first pre-product Beta@Pt-W.

[0092] (2) 1 g of the first pre-product was mixed with 0.31 g of tetraethyl orthosilicate (TEOS) calculated as SiO2, 0.5 g of sodium hydroxide, 1 g of tetraethylammonium hydroxide (structure directing agent), 0.02 g of sodium aluminate calculated as alumina, and 2 g of water, stirred and aged at room temperature for 8 hours, and then transferred to a hydrothermal reactor for crystallization reaction at 140° C. for 36 hours to obtain a second pre-product;

[0093] (3) The second pre-product is centrifuged, dried, and calcined at 450° C. for 3 h to obtain a Beta@Pt-W@Beta metal-encapsulated micro-mesoporous molecular sieve catalyst.

[0094] Figure 1 is a TEM image of the metal-encapsulated micro-mesoporous molecular sieve catalyst of Example 1. Figure 1 It can be seen that the Pt nanoparticles are encapsulated inside the molecular sieve rather than on the outer surface.

[0095] Figure 2 is the pore distribution diagram of the metal encapsulated micro-mesoporous multi-level pore molecular sieve catalyst of Example 1, from Figure 2 It can be seen that the catalyst has a multi-level pore structure with coexistence of micropores and mesopores.

[0096] Example 2

[0097] The catalyst was prepared according to the method of Example 1, except that the silicon source in step (2) was replaced by white carbon black providing the same mass of SiO2 as in Example 1, the first alkali source was replaced by potassium hydroxide with the same mass as in Example 1, the structure directing agent was ammonium bromide with the same mass as in Example 1, and other conditions were the same as in Example 1, to obtain Beta@Pt-W@Beta metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst.

[0098] Example 3

[0099] The catalyst was prepared according to the method of Example 1, except that in step (2), the same mass of silicon source and aluminum source as in Example 1 were first used, 0.5 g of ammonia water and 3 g of water were added, and the mixture was stirred and aged at room temperature for 8 hours. Then, 5 g of tetraethylammonium hydroxide (structure directing agent) was added and the mixture was transferred to a hydrothermal reactor and crystallized at 140°C for 36 hours to obtain a second pre-product. The other conditions were the same as in Example 1 to obtain a Beta@Pt-W@Beta metal-encapsulated micro-mesoporous multi-level pore molecular sieve catalyst.

[0100] Example 4

[0101] (1-1) A sodium tungstate solution containing 0.1 g of WO3 was mixed with 10 g of ZSM-5 zeolite molecular sieve and stirred for 4 h. The average particle size of the ZSM-5 zeolite molecular sieve was 0.3 μm, and the silicon-aluminum ratio SiO2 / Al2O3 was 15. After rotary evaporation and drying, the mixture was calcined at 600°C in air for 3 h to obtain a core loaded with W oxide.

[0102] (1-2) 300 mL of 80% ethanol aqueous solution (solvent) was placed in a 500 mL round-bottom flask, 0.1 g of Pt was added through a chloroplatinic acid solution, 1 g of polyvinyl pyrrolidone (template) was added, and the mixture was stirred for 5 min, then heated to 90 °C and refluxed for 3 h under an argon atmosphere to obtain a Pt nanoparticle solution;

[0103] 1 g of the W oxide-loaded core was added to a solution containing 0.02 g of Pt nanoparticles, stirred for 3 h under ultrasonic conditions, centrifuged, and dried at 100 °C for 8 h to obtain the first pre-product ZSM-5@Pt-W.

[0104] (2) 1 g of the first pre-product was mixed with 0.23 g of tetramethyl silicate (silicon source) calculated as SiO2, 0.5 g of potassium hydroxide (alkali), 0.5 g of tetrapropylammonium hydroxide (structure directing agent), and 0.02 g of pseudo-boehmite (aluminum source) calculated as alumina, and aged at room temperature for 8 hours, and then transferred to a hydrothermal reactor for crystallization reaction at 170° C. for 24 hours to obtain a second pre-product;

[0105] (3) The second pre-product is centrifuged, dried, and calcined at 500° C. for 3 h to obtain a ZSM-5@Pt-W@ZSM-5 metal-encapsulated micro-mesoporous molecular sieve catalyst.

[0106] Example 5

[0107] The catalyst was prepared according to the method of Example 1, except that in step (1-2), Pt nanoparticles were loaded on the W oxide-loaded core by an equal volume impregnation method. Specifically, 2 g of the core was impregnated with 2 mL of a Pt nanoparticle solution containing 0.03 g of Pt. Other conditions were the same as in Example 1 to obtain a catalyst.

[0108] Example 6

[0109] The catalyst was prepared according to the method of Example 1, except that step (1-1) was not performed, and the same mass of ammonium metatungstate as in Example 1 was directly added to the Pt nanoparticle solution of step (1-2) and loaded onto the same mass of Beta molecular sieve cores. Other conditions were the same as in Example 1 to obtain the catalyst.

[0110] Comparative Example 1

[0111] The catalyst was prepared according to the method of Example 1, except that step (2) was not performed, and the first pre-product of step (1) was directly dried and heat-treated. Other conditions were the same as those of Example 1, and a catalyst without a zeolite molecular sieve outer layer was obtained.

[0112] Test Example 1

[0113] The structural parameters and active component contents of the catalysts prepared in the examples and comparative examples are shown in Table 1.

[0114] Table 1

[0115]

[0116] It can be seen from Table 1 that the Pt content of the metal encapsulated molecular sieve catalyst hardly changes after 720 hours of long-term operation, while the Pt content of the comparative catalyst without shell protection loses 15wt% after 720 hours of reaction.

[0117] Test Example 2

[0118] 1 g of the catalysts obtained in the embodiment and the comparative example were weighed respectively and placed in a fixed bed reactor. Under the conditions of reaction temperature of 160° C. and hydrogen pressure of 4 MPa, the mass space velocity of the glycerol aqueous solution was 1 h -1 , a 50 wt % glycerol aqueous solution was introduced, and the liquid at the outlet after 8 h and 720 h of reaction was taken for gas chromatography analysis. The results are shown in Table 2.

[0119] Table 2

[0120]

[0121] It can be seen from the results in Table 2 that the catalyst prepared by the embodiment of the present invention, used for hydrogenolysis of glycerol to produce 1,3-propylene glycol, has higher hydrothermal stability than the catalyst synthesized by the existing method, and the glycerol conversion rate, the selectivity of 1,3-propylene glycol in the product and the catalyst stability are significantly improved.

[0122] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A metal-encapsulated micro-mesoporous molecular sieve catalyst, characterized in that: The catalyst comprises a molecular sieve seed core, an interlayer containing active components and a zeolite molecular sieve shell; Wherein, the interlayer containing active components includes W oxide and Pt nanoparticles.

2. The catalyst according to claim 1, wherein The molecular sieve seed core is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, preferably Beta molecular sieve and / or HY molecular sieve; Preferably, the average particle size of the molecular sieve seed core is 0.1-10 μm, preferably 0.2-2 μm; Preferably, the average particle size of the Pt nanoparticles is 0.5-8 nm, preferably 2-4 nm; Preferably, based on the total weight of the catalyst, the mass percentage of the Pt nanoparticles is 0.2-5wt%, preferably 1-2wt%; Preferably, based on the total weight of the catalyst, the mass percentage of the W oxide is 0.2-5wt%, preferably 0.5-2wt%.

3. The catalyst according to claim 1 or 2, wherein The thickness of the molecular sieve shell is 5-80nm, preferably 10-30nm; Preferably, the mesopore volume of the metal-encapsulated multi-level zeolite molecular sieve is 0.01-0.1m 3 / g, preferably 0.03-0.08m 3 / g; micropore volume is 0.03-0.3m 3 / g, preferably 0.05-0.1m 3 / g; Preferably, the shell molecular sieve is at least one selected from Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve.

4. A method for preparing a metal-encapsulated micro-mesoporous multi-level molecular sieve catalyst, characterized in that: The method comprises: (1) loading W oxide and Pt nanoparticles on the molecular sieve seed core to obtain a first pre-product; (2) subjecting a mixed solution containing the first pre-product, the first alkali source, the structure directing agent, the silicon source, the aluminum source and water to a crystallization reaction to obtain a second pre-product; (3) heat-treating the second pre-product to obtain a molecular sieve catalyst.

5. The preparation method according to claim 4, wherein The loading process in step (1) includes: (1-1) mixing a W precursor solution with a molecular sieve seed core, drying and calcining to obtain a core loaded with W oxide; (1-2) mixing and ultrasonically treating the W oxide-loaded core and the Pt nanoparticle solution, and then drying to obtain a first pre-product; Preferably, the molecular sieve seed core is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, preferably Beta molecular sieve and / or HY molecular sieve; Preferably, the W precursor is selected from at least one of ammonium metatungstate, ammonium paratungstate and sodium tungstate; Preferably, the amount of the W precursor added is calculated as oxide, and the mass ratio of the W precursor to the molecular sieve seed core is 1:20-500, preferably 1:50-200; Preferably, the calcination conditions include: calcination temperature of 400-700°C, calcination time of 1-10h; Preferably, the mass ratio of the molecular sieve seed core loaded with W oxide to the Pt nanoparticles is 1:0.002-0.04, preferably 1:0.01-0.02; Preferably, in step (1-2), the drying conditions include: heating temperature of 40-120°C, preferably 60-100°C; heating time of 1-15h, preferably 3-10h.

6. The preparation method according to claim 5, wherein: The preparation method of the Pt nanoparticle solution comprises: mixing a Pt source, a template agent and a solvent, and refluxing to obtain a Pt nanoparticle solution; Preferably, the amount of the Pt source added is calculated as Pt single substance, and the mass ratio of the Pt source: template: solvent is 1: (1-50): (500-10000), preferably 1: (5-30): (1000-5000); Preferably, the reflux conditions include: under a protective atmosphere, a reflux temperature of 60-200° C., preferably 80-180° C.; a reflux time of 0.5-6 h, preferably 2-4 h; Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate and potassium chloroplatinate; Preferably, the solvent is selected from at least one of an aqueous alcohol solution of a saturated monohydric alcohol having 1 to 3 carbon atoms and an aqueous solution of a saturated dihydric alcohol having 1 to 3 carbon atoms, preferably selected from at least one of an aqueous methanol solution, an aqueous ethanol solution and an aqueous propanol solution.

7. The preparation method according to any one of claims 4 to 6, wherein: In step (2), in the mixed solution, the amount of the silicon source added is calculated as SiO2, the amount of the aluminum source added is calculated as Al2O3, and the mass ratio of the first pre-product: the first alkali source: the structure directing agent: the silicon source: the aluminum source: the water is 1: (0.1-10): (0.1-10): (0.05-1): (0.005-0.1): (1-10), preferably 1: (0.2-5): (0.2-5): (0.1-0.5): (0.01-0.05): (2-5); Preferably, the structure directing agent is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium bromide and tetrapropylammonium bromide; Preferably, the silicon source is ethyl orthosilicate and / or methyl orthosilicate; Preferably, the aluminum source is sodium aluminate and / or pseudo-boehmite.

8. The preparation method according to any one of claims 4 to 7, wherein: Step (2) further includes an aging process before the crystallization reaction, wherein the aging conditions include: an aging time of 1-16 hours, preferably 5-12 hours; Preferably, the conditions of the crystallization reaction include: reaction temperature of 80-240°C, preferably 120-180°C; reaction time of 2-120h, preferably 12-36h; Preferably, in step (3), the heat treatment conditions include: heating temperature of 200-600°C, preferably 300-500°C; heating time of 1-10h, preferably 3-6h.

9. The metal-encapsulated micro-mesoporous molecular sieve catalyst prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the metal-encapsulated micro-mesoporous molecular sieve catalyst according to any one of claims 1 to 3 and 9 in the reaction of synthesizing 1,3-propylene glycol.

11. A method for synthesizing 1,3-propylene glycol, characterized in that: The method comprises: contacting a glycerol aqueous solution with the metal-encapsulated micro-meso-hierarchical pore molecular sieve catalyst as claimed in any one of claims 1 to 3 and 9 to react; Preferably, the reaction conditions include: reaction temperature of 120-200°C, preferably 150-170°C; hydrogen pressure of 1-6MPa, preferably 3-5MPa; mass concentration of glycerol in the glycerol aqueous solution of 10-95wt%, preferably 40-90wt%; liquid phase mass space velocity of 0.05-5h -1 , preferably 0.1-2h -1 .

Citation Information

Patent Citations

  • Process for the biological production of 1,3-propanediol with high yield

    CN100471946C

  • Method for producing 1,3-propylene glycol through using glycerin of by-product from biologic diesel oil

    CN1327001C

  • Multistage pore structure nano molecular sieve catalyst and preparation method thereof

    CN102000601A

  • Supported meso-porous molecular sieve catalyst, and preparation method and application thereof

    CN107159300A

  • Molecular sieve packaged core-shell catalyst and preparation method thereof

    CN114749207A

Cited By

  • Core-interlayer-shell structure catalyst with stepped communicated pore channels and preparation method of core-interlayer-shell structure catalyst

    CN122352333A